O tratamento jurídico do consumo sustentável no Brasil e a proposta de uma abordagem complexa pelo Direito dos Resíduos - Gonçalves, Carla Maria Barreto (2021)
The correlation between the environmental crisis and unsustainable consumption patterns is increasingly evident, as well as the urgent need to prevent the worsening of the situation. However, the prevalence of a simplifying approach to the subject is perceived, which, anchored in the modern scientific model, which is Cartesian, mechanistic and, especially, reductionist; and it is replicated in the subject's legal discipline. However, it has been verified how this knowledge model is limited and disregards the complexities inherent to consumption and the ecological crisis. Thus, an adequate understanding of consumption practices and their respective environmental damage is required. Therefore, there is the starting question: to what extent is the legal treatment of Sustainable Consumption in Brazil compromised by the simplifications of the scientific reductionist and how could it adapt to the complexity of sustainable consumption? To answer it, it is first investigated how the economic and legal visions are consolidated, based on the modern scientific model, its main criticisms and influences on the measures of implementation and understanding of Sustainable Consumption, when the proposals for complexity by Enrique Leff and Edgar Morin. Then, the central aspects of Brazilian law in the treatment of Sustainable Consumption are investigated, its limitations and how to overcome them in its simplifying trends, an opportunity to reflect on the influences of post- modern and the need for a more pragmatic understanding of the Brazilian reality. Finally, through the adoption of a classification of consumption activities, we identify the environmental impacts and the urgency to pay greater attention to the generation of solid urban waste taking in consideration the products life cycle. Hence, Waste Law, as a new field within the Environmental Law which interacts with other law fields, shows itself as the solution to the complex approach. Furthermore, possible pandemic impacts of COVID-19 in the consolidation of the proposed complex approach are also evaluated. It is concluded that the simplified view of consumption and the environmental crisis can, and must, be overcome, imposing the recognition of its complexity. Therefore, the complex approach proves to be possible, and necessary, mainly under the logic of waste generation, which appreciates the product's life cycle from extraction to the final residuality of the materials, which must be reused. The methodology adopted was a systematic literature review, in which academic works, normative instruments and institutional reports related to the subject were analyzed.